2012
DOI: 10.4322/natcon.2012.013
|View full text |Cite
|
Sign up to set email alerts
|

How Sustainable Is The Use of Natural Resources in Brazil?

Abstract: The concept of sustainability is that present use of a resource would not prevent it being available for future generations. For exploited biological populations, sustainability is a demographic question. Herein we reviewed studies (released 1987-2010) evaluating presumably sustainable use of timber, hunting and non-timber forest products (NTFP) in Brazil. The studies analysed 239 cases (each case being one species evaluated in one study). Sustainability could be evaluated only in 126 cases studied with a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 19 publications
0
15
0
8
Order By: Relevance
“…This potential can only be determined through monitoring in the long term systems components, particularly those of biological populations. In this way, in the majority of actions labelled or deemed "sustainable", sustainability has always been assumed, and has not been tested or demonstrated (FERNANDEZ, 2005;FERNANDEZ et al, 2012;MORSE, 2010;PERES et al, 2003). Ways of exploiting resources are labelled "sustainable" on a recurring basis that may have a lesser ecological impact than other more destructive means of exploitation.…”
Section: Sustainabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This potential can only be determined through monitoring in the long term systems components, particularly those of biological populations. In this way, in the majority of actions labelled or deemed "sustainable", sustainability has always been assumed, and has not been tested or demonstrated (FERNANDEZ, 2005;FERNANDEZ et al, 2012;MORSE, 2010;PERES et al, 2003). Ways of exploiting resources are labelled "sustainable" on a recurring basis that may have a lesser ecological impact than other more destructive means of exploitation.…”
Section: Sustainabilitymentioning
confidence: 99%
“…Ways of exploiting resources are labelled "sustainable" on a recurring basis that may have a lesser ecological impact than other more destructive means of exploitation. However, a less damaging form of use does not necessarily imply sustainability (FERNANDEZ, 2005;FERNANDEZ et al, 2012).…”
Section: Sustainabilitymentioning
confidence: 99%
“…We applaud Fernandez et al (2012) for their valuable article in the recent issue of Natureza & Conservação, pointing out that about half of the endeavors of natural resource extraction labeled as "sustainable", in Brazil, are actually unsustainable. The article perfectly exemplifies the metaphors of Trojan horses and false friends.…”
mentioning
confidence: 99%
“…Such chemical elements are essential for proper ecosystem functioning, and their export from anthropogenic activities results in a gradual deterioration of ecosystem capacity to retain its processes and biodiversity (DeAngelis 1992;Flueck et al 2012). Thus, demographic analyses showed that forest harvesting based on 30 year rotations as defined by Brazilian law for Amazonia were too short (Fernandez et al 2012), yet the additional consideration of skewed nutrient concentrations principally in biomass in such areas would indicate much larger effects from biophysical limits. Elsewhere, at harvest intervals of 35 years, up to 62% of the total nutrient pool was removed (Dyck & Cole 1994).…”
mentioning
confidence: 99%
See 1 more Smart Citation